2018
DOI: 10.1097/pcc.0000000000001476
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Post Intensive Care Syndrome in Children—The PICS-p Framework*

Abstract: Post Intensive Care Syndrome in pediatrics will help illuminate the phenomena of surviving childhood critical illness and guide outcomes measurement in the field. Empirical studies are now required to validate and refine this framework, and to subsequently develop a set of core outcomes for this population. With explication of Post Intensive Care Syndrome in pediatrics, the discipline of pediatric critical care will then be in a stronger position to map out recovery after pediatric critical illness and to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
287
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 305 publications
(335 citation statements)
references
References 14 publications
6
287
0
15
Order By: Relevance
“…In 2018, the framework of pediatric PICS (PICS‐p) was conceptualized (Fig. ) . The fundamental framework was similar to that of adult PICS, with several unique features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, the framework of pediatric PICS (PICS‐p) was conceptualized (Fig. ) . The fundamental framework was similar to that of adult PICS, with several unique features.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a variety of recovery trajectories of surviving children and their families are indicated in the PICS‐p framework, including improvement, deterioration, vacillation, or plateau over days or decades. Available evidence, although still limited, suggests that their outcomes are more heterogeneous than those for adult ICU survivors and their spouses …”
Section: Introductionmentioning
confidence: 99%
“…4 In addition to morbidity in children after admission to the PICU, parents and families are faced with substantial stress when their children are admitted to the PICU 1 and are at risk for developing postintensive care syndrome in pediatrics (PICS-p), which is a recently described framework to understand surviving childhood critical illness with a focus on the interdependence of children and their families. 3,5,6 Parents identify stress surrounding a change in their children' s appearance and behavior and especially due to an alteration in their parental role when their children have been admitted to the PICU. 1,7 Parent stress continues after discharge from the hospital 7 and can include psychiatric disorders.…”
mentioning
confidence: 99%
“…Parents carry much of the burden of care and worry associated with caring for these children. Studies of experiences of parents of children with respiratory distress who require bronchoscopy are rare, even though studies of children with respiratory distress or critical illness admitted to a paediatric intensive care unit have demonstrated that parents experience stress and anxiety in response to multiple stressors arising from the child's illness trajectory (Foster et al ., ; Terp and Sjöström‐Strand, ) and post‐traumatic stress disorder or symptoms resulting from being aware of or witnessing the intrusive treatment given to the child (Nelson and Gold, ; Manning et al ., ). They may report feelings of alienation and uncertainty in relation to use of hospital systems and care (Caicedo, ; Simeone et al ., ), and a recent survey reported that the stress levels of primary caregivers with oxygen‐dependent children is high.…”
Section: Introductionmentioning
confidence: 97%